2012
DOI: 10.4049/jimmunol.1103324
|View full text |Cite
|
Sign up to set email alerts
|

Lymphotoxin β Receptor Activation on Macrophages Induces Cross-Tolerance to TLR4 and TLR9 Ligands

Abstract: Our previous studies indicated that lymphotoxin β receptor (LTβR) activation controls and downregulates inflammatory reactions. In this study, we report that LTβR activation on primary mouse macrophages results in induction of tripartite motif containing (TRIM) 30α, which negatively regulates NF-κB activation induced by TLR signaling. LTβR activation results in a downregulation of proinflammatory cytokine and mediator expression upon TLR restimulation, demonstrating that LTβR signaling is involved in the induc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
38
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(40 citation statements)
references
References 41 publications
1
38
1
Order By: Relevance
“…The agonist-mediated activation of LTβR signaling in macrophages has been shown previously to inhibit their capability to upregulate NO and cytokine production upon re-stimulation with lipopolysaccharide in vitro [42]. This suggests that the downregulation of iNOS, TNFα and IFNγ in MAMs in our model may occur through a direct interaction between LTβ on cancer cells and the LTβR on MAMs.…”
Section: Discussionmentioning
confidence: 61%
See 1 more Smart Citation
“…The agonist-mediated activation of LTβR signaling in macrophages has been shown previously to inhibit their capability to upregulate NO and cytokine production upon re-stimulation with lipopolysaccharide in vitro [42]. This suggests that the downregulation of iNOS, TNFα and IFNγ in MAMs in our model may occur through a direct interaction between LTβ on cancer cells and the LTβR on MAMs.…”
Section: Discussionmentioning
confidence: 61%
“…LTβ was the most suitable candidate because (i) it was the most significantly differentially expressed cytokine (~45-fold) between the brain parenchyma- and dura-derived 4T1 cancer cell variants; (ii) its role in the regulation of inflammatory microenvironments in secondary lymphoid organs is well established [39]; (iii) recent data linked LTβ to inflammation-induced carcinogenesis [41] and (iv) the agonist-induced activation of LTβR on macrophages has been previously linked to a reduction in their nitric oxide (NO) and cytokine production in vitro [42]. …”
Section: Resultsmentioning
confidence: 99%
“…prising, since other intestinal cells, such as mucosal macrophages, are barely responsive to TLR ligands to avoid excessive release of inflammatory mediators in response to leaking bacterial products (55).…”
Section: Discussionmentioning
confidence: 99%
“…It has been previously reported that TLR responses can be inhibited by extracellular stimuli such as cytokines 39 or integrin ligation 40,41 . Since Cdc42 activation occurs downstream integrin, receptor tyrosine kinase or G-protein-coupled receptors signaling 42 , it could affect actin polymerization and the anchoring of CpG + -TLR9 + endosomes by IRAP.…”
Section: ! Disscussionmentioning
confidence: 99%